Quadratus Lumborum Block versus Fascia Iliaca Compartment Block for Acetabular Fracture Surgery by Stoppa Method: A Double-Blind, Randomized, Noninferiority Trial - Mirkheshti, Alireza; Hashemian, Morteza; Abtahi, Dariush; Shayegh, Sara; Manafi-Rasi, Alireza; Sayadi, Shahram; Memary, Elham; Karami, Nazli; Rostamian, Baharak; Shakeri, Alireza (Pain Research and Management, 2024)
Background. Acetabular fracture surgeries are frequently accompanied by protracted and severe perioperative pain, and there is no consensus on optimal pain relief management. Aim. This study aimed at comparing the analgesic efficacy of fascia iliaca compartment block (FICB) and quadratus lumborum block (QLB) in patients with acetabular fractures undergoing surgery using the Stoppa method. Methods. In this double-blind, randomized, noninferiority clinical trial, adult patients undergoing spinal anesthesia for acetabular fracture surgery, in Imam Hossein Hospital, Tehran, Iran (IRCT20191114045435N1), were randomly divided into two groups: FICB (n = 22) and QLB (n = 24). The visual analog scale (VAS) was used to assess the pain intensity at different times for all participants. In addition, the dose of fentanyl required to induce the patient to sit for spinal anesthesia and the pain intensity were evaluated. Moreover, the duration of analgesia and the total amount of morphine consumed in the first 24 h following surgery were evaluated, analyzed, and compared between the two study groups. Results. FICB and QLB demonstrated effective comparative postoperative analgesic profiles following acetabular fracture surgery; however, no significant differences in VAS values were observed between the two groups during the study. FICB experienced reduced cumulative fentanyl consumption during spinal anesthetic placement, whereas QLB had a significantly lower total morphine demand in the initial postoperative 24 h period. Conclusion. The lateral QLB and FICB can be introduced as effective routes for analgesia in acetabular fracture surgery using the Stoppa method. Clinical Trial Registration. The study was prospectively registered in the clinical trials registry system, on 2021-02-17, with registration number: IRCT20191114045435N1.